Pharmaceutical Education and Rational Drug Use Patterns in Urban Kirkuk: Pendidikan Farmasi dan Pola Penggunaan Obat yang Rasional di Kota Kirkuk - Sara Assif Younis; Suren Azad Ramadhan; Karez Abdulghany Omer; Muhannad Omer Taher; Rawand Sirwan Izzalddin; Diyar Salahuddin Ali (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Irrational drug use remains a major public health concern in low- and middle-income countries. Specific Background: In conflict-affected regions such as Kirkuk, limited regulation and widespread self-medication exacerbate unsafe practices. Knowledge Gap: Empirical evidence linking pharmaceutical education to rational drug use in such contexts remains scarce. Aim: This study examined the relationship between pharmaceutical education and knowledge, attitudes, and practices regarding medication use among Kirkuk residents. Results: A cross-sectional survey of 200 participants revealed that higher educational attainment was significantly associated with safer medication behaviors (p < 0.05), including instruction reading and pharmacist consultation, although irrational practices persisted. Novelty: This study provides rare data from a conflict-affected Middle Eastern urban setting. Implications: Findings highlight the need for integrated, culturally responsive educational and regulatory strategies to promote rational drug use beyond knowledge acquisition alone. Highlights:• Pharmaceutical education improves awareness but does not eliminate irrational drug use• Younger adults show higher self-medication tendencies• Gender and education significantly shape medication practices Keywords: Pharmaceutical Education, Rational Drug Use, Self-Medication, Community Health, Iraq